Gender politics in transitional justice - O'Rourke, Catherine (Milton Park, Abingdon, Oxon : Routledge, 2013)
'Transitions from violent conflict and authoritarian rule are believed to be transformative moments for women, unique conjunctures in public and private, international law and domestic law, with the potential to transform the gender order of a society. Transitional justice processes, though principally concerned with providing limited accountability for human rights violations of the past, are increasingly injected with transformative social and political goals for the future. What then is the impact of transitional justice processes on the human rights of women in states emerging from political violence? Gender Politics in Transitional Justice draws on original comparative research on women's movements in Chile, Northern Ireland, and Colombia, and on legal analysis of transitional justice processes in these case studies, to answer these questions. Catherine O'Rourke argues that human rights outcomes for women of transitional justice processes are negotiated and determined in the space between international law and local gender politics'--
Between international law and local gender politics : women's human rights in transitional justice -- Justice for what? : Recognizing a web of gender-based harms against women in transitional justice -- Defining'justice' : patterns in human rights advocacy -- Criminal accountability and harms against women -- Feminist truth strategies : looking backward, moving forward -- Global standards, local truths : harms against women in truth processes -- Women's movements claiming repair -- Reparations in transitional justice and harms against women -- Women's movements seeking institutional reform -- Institutional reform and harms against women.
'A GlassHouse book'
Includes bibliographical references (pages 249-270) and index.
Keywords: Transitional justice; Women -- Legal status, laws, etc